2023
DOI: 10.2147/jir.s411086
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio are Important Indicators for Predicting in-Hospital Death in Elderly AMI Patients

Abstract: To investigate the role of neutrophil-to-lymphocyte ratio(NLR) and platelet-to-lymphocyte(PLR) in predicting the risk of inhospital mortality in elderly acute myocardial infarction(AMI) patients. Methods: This study was a single-center, retrospective and observational study. From December 2015 to December 2021, a total of 1550 elderly patients (age ≥ 60 years) with AMI with complete clinical history data were enrolled in the Second Hospital of Dalian Medical University. Routine blood tests were performed on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…A study by Bhat et al demonstrated that a higher NLR is associated with increased mortality among patients with congestive heart failure [ 30 ]. Our study’s findings are consistent with those of these previous studies, indicating an elevated NLR’s association with increased CVD risk [ 29 , 30 ]. Furthermore, a study by Chen et al suggested that NLR and PLR can predict in-hospital mortality risk in elderly patients with acute myocardial infarction, with NLR showing better predictive ability than PLR [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A study by Bhat et al demonstrated that a higher NLR is associated with increased mortality among patients with congestive heart failure [ 30 ]. Our study’s findings are consistent with those of these previous studies, indicating an elevated NLR’s association with increased CVD risk [ 29 , 30 ]. Furthermore, a study by Chen et al suggested that NLR and PLR can predict in-hospital mortality risk in elderly patients with acute myocardial infarction, with NLR showing better predictive ability than PLR [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study’s findings are consistent with those of these previous studies, indicating an elevated NLR’s association with increased CVD risk [ 29 , 30 ]. Furthermore, a study by Chen et al suggested that NLR and PLR can predict in-hospital mortality risk in elderly patients with acute myocardial infarction, with NLR showing better predictive ability than PLR [ 29 ]. Similarly, our study found that NLR remained significantly associated with an increased risk of CVD even after adjusting for several factors, whereas PLR lost its significance after these adjustments.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations